Structural and biophysical investigations of Rab GTPase interacting proteins - Dregger, Carmen (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2011)
Summary: Rab GTPases are important regulators of cell trafficking steps such as vesicle fusion, budding and motility. They are often described as 'on/off' switches, interacting with specific effectors when bound to GTP. Although their secondary and tertiary structures are largely conserved they bind sometimes very diverse effectors sharing little or no homology. A similar but less prodigious situation is evident with guanosine nucleotide exchange factors, proteins that interact with Rab GTPases in order to facilitate the nucleotide exchange during the Rab GTPase cycling.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin.